PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, DAN PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Empiris Pada SKPD Provinsi Riau) - Dicky Rahman; Hardi -; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aim to analyze the impact of empirical utilization of information technology, the application of region’s Financial Accounting System and application of the government accounting standards on the quality of region’s financial reporting area in Riau province. Analysis method used in this research was multiple regression using SPSS Version 20. Population in this research is the all of Echelon III and IV Unit in the Riau provincial government amounting to 1063 people. Respondents of this research is some have maintained echelon III and IV in each SKPD (satuan kerja perangkat daerah) Riau Province. Echelon III and IV was chosen as respondents with the reason to look at managerial performance in the financial quality reporting area. Results of this research is the utilization of information technology, Implementation of Region’s Financial Accounting System , Implementation of the Government Accounting Standards significantly positive affects the quality of the region's financial reporting that can be viewed by t> t table.Keywords: Information Technology, Accounting, Government, Quality and Reporting.